The Performance of AlCC as an Order Selection Criterion in ARMA Time Series Models - Sen, Liew Khim; Shitana, Mahendran (Universiti Putra Malaysia Press, 2002)
This study is undertaken with the objective of investigating the performance of Akaike's Information Corrected Criterion (AlCC) as an order determination criterion for the selection of Autoregressive Moving-Average or ARMA (P,q) time series model. A simulation investigation was carried to determine the probability of the AlCC statistics picking up the correct model. Result obtained showed that the probability of the AlCC criterion picking up the correct model was moderately good. The problem of over parameterization existed but under parameterization was found to be minimal. Hence, for any two comparable models, it is always safe to choose the one with lower order of p and q.